Review and Implementation of Technology for Solid Radioactive Waste Volume Reduction - Spargo, Barry J.; Krumrine, Paul (1999)
Arctic Military Environmental Cooperation (AMEC) Project 1.3 is developing solutions to minimize the impact of solid radioactive waste (SRW) resulting from nuclear submarine decommissioning on the Arctic environment. During 1999, the project direction has shifted and become more focused as the Russian shipyard needs have become better defined within the budgetary realities of the program. The result of this shift is the concept of a mobile pretreatment facility (MPF) that would permit solid waste sorting, volume reduction and containerization at current storage locations on the Kola Peninsula prior to transfer to a central processing facility (CPF) for final treatment and disposal. This is an important first step to stabilize the waste and reduce its volume so that ongoing decommissioning activities can continue. The CPF while still a goal of the project would entail a major expenditure of funds which is likely beyond the current AMEC program capabilities. However, the engineering assessment and planning of the CPF is within the current scope to ensure full compatibility and integration with the MPF operation. The original document contains color images.